#### Answer

See the picture below.

#### Work Step by Step

By calculating the values of $f(x)=3\sqrt{x}-2$ (with blue) and $g(x)=\sqrt{x}$ (with red) we can see that the following equation is true for every x value: $3g(x)-2=f(x)$.
In order to graph the exact parent graph, here is the table of values:
$g(0)=\sqrt0=0$
$g(1)=\sqrt1=1$
$g(2)=\sqrt2=\sqrt2$
$g(3)=\sqrt3=\sqrt3$
$g(4)=\sqrt4=2$
(The square root function is not defined for negative numbers.)
Therefore the graph of $f(x)$ is exactly the same as the graph of $g(x)=\sqrt x$ but is wider (is stretched vertically by a factor of 3) and is translated 2 units down.